2020
DOI: 10.1111/cobi.13469
|View full text |Cite
|
Sign up to set email alerts
|

An ecological framework for contextualizing carnivore–livestock conflict

Abstract: Carnivore predation on livestock is a complex management and policy challenge, yet it is also intrinsically an ecological interaction between predators and prey. Human-wildlife interactions occur in socioecological systems in which human and environmental processes are closely linked. However, underlying human-wildlife conflict and key to unpacking its complexity are concrete and identifiable ecological mechanisms that lead to predation events. To better understand how ecological theory accords with interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 82 publications
1
39
0
5
Order By: Relevance
“…To make progress toward human–wildlife coexistence, a better understanding and objective testing of assumptions about the causes of wildlife‐induced damages from various perspectives, including wildlife ecology, human perceptions and behavior, and legal frameworks (Chapron & López‐Bao 2020; Treves & Santiago‐Ávila 2020 [this issue]; Wilkinson et al. 2020 [this issue]) is essential. This is particularly important in landscapes where people have modified nature in such a way that agriculture provides habitat to some (protected) species and where novel governance models are needed to balance shared land use between people and wildlife.…”
Section: Call For Governance Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…To make progress toward human–wildlife coexistence, a better understanding and objective testing of assumptions about the causes of wildlife‐induced damages from various perspectives, including wildlife ecology, human perceptions and behavior, and legal frameworks (Chapron & López‐Bao 2020; Treves & Santiago‐Ávila 2020 [this issue]; Wilkinson et al. 2020 [this issue]) is essential. This is particularly important in landscapes where people have modified nature in such a way that agriculture provides habitat to some (protected) species and where novel governance models are needed to balance shared land use between people and wildlife.…”
Section: Call For Governance Structuresmentioning
confidence: 99%
“…2020 [this issue]; Tsunoda & Enari 2020 [this issue]; Wilkinson et al. 2020) and transboundary PAs and areas surrounding PAs (Jordan et al. 2020 [this issue]; Martínez‐Jauregui et al.…”
Section: Agriculture and Conservation Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…Ecologists have demonstrated that heterogeneous environments produce differential risks of predation, and that habitat characteristics, topography, ambush points, and other such landscape features are essential to the spatial patterning of predation risk (Brown, 1999; Gaynor et al, 2019; Trainor, Schmitz, Ivan, & Shenk, 2014). More recent research has applied these ecological theories to livestock predation (Kluever, Breck, Howery, Krausman, & Bergman, 2008; Kluever, Howery, Breck, & Bergman, 2009; Laporte, Muhly, Pitt, Alexander, & Musiani, 2010; Shrader, Brown, Kerley, & Kotler, 2008; Wilkinson et al, in press). In particular, the rapidly growing field of predation risk modeling uses statistical approaches from wildlife ecology to generate predictive, spatially explicit maps of livestock predation risk as it varies over a landscape (Miller, 2015; Treves & Naughton‐Treves, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Predation risk is thus a function of both ecological characteristics and human decisions and the interactions between the two, meaning that an accurate understanding of livestock predation risk patterns must be gained through a socio‐ecological lens. Ecological studies of livestock predation are still in need, and have important potential to reveal blind spots for livestock producers and managers regarding the circumstances and drivers of conflict (Wilkinson et al, in press). However, strictly ecological approaches may suffer from selection bias, in which available data do not represent the system, if they do not explicitly incorporate producer decisions regarding the distribution of livestock, and thus livestock predation.…”
Section: Introductionmentioning
confidence: 99%